Improved Charge Injection of Metal Oxide Thin‐Film Transistors by Stacked Electrodes of Indium Tin Oxide Nanoparticles and Silver Nanowires. (25th January 2018) - Kim, Chaewon; Kim, Yong‐Hoon; Noh, Yong‐Young; Hong, Sung‐Jei; Lee, Mi Jung
Abstract: Solution processed transparent electrodes are developed combining indium tin oxide nanoparticles (ITO‐NPs) and silver nanowires (Ag NWs) at low process temperature of 100 °C, compatible with solution processed indium gallium zinc oxide (IGZO) thin‐film transistors as source and drain electrodes. Four structures with various stacking of ITO‐NPs and Ag NWs are investigated. Although sole ITO‐NPs cannot provide the conductivity electrical properties of devices, including the mobility, threshold voltage, and subthreshold swing, are improved using ITO‐NPs over/under the Ag NWs. The mobility is enhanced by employing a hybrid electrode structure from 0.004 cm 2 V −1 s −1 (single layer) to 3.42 cm 2 V −1 s −1 (triple layer). The ultraviolet photoelectron spectroscopy and UV–vis measurements reveal the electronic structure to confirm the increase of charge carrier concentration at the interface, when ITO‐NP/IGZO heterojunction is formed. The ITO‐NP layer acts as a buffer layer between the IGZO and Ag NWs layer to facilitate charge injection to reduce the contact resistance, while the Ag NWs supply conductivity. These are also confirmed by Hall measurement and contact resistance extraction. Hybrid electrodes developed here are promising approach for solution processed transparent electrodes toward transparent and flexible electronics with advantages of low‐cost process excluding vacuum system. Abstract : Indium tin oxide nanoparticles ink is spin coated as a buffer layer to improve charge injection in indium gallium zinc oxide thin film transistors combining silver nanowires to achieve fully solution processed transparent electrodes at low process temperature of 100 °C. Electrical characterization and ultraviolet photoelectron spectroscopy analysis is carried out to prove it.